The Radii and Densities of Elementary Particles and Periodic Table Nucleons (London Journal of Research In Science: Natural and Formal, 2025)
We calculate the size as the radius of a sphere, along with the density of all the elementary particles of the first column of the Standard Model of Particle Physics viz. the Up and Down quarks, the electron, the electron neutrino, the proton, the neutron, and the nuclei of all the elements and isotopes of the Periodic Table, using their known masses and the previously calculated radii (r) of the electron and the electron neutrino since re/re = me/me, can be extended further to calculate rp, rn, rUp,  rDown and their densities, and rNucleon Number with a Table of nucleon radii that increase and nucleon density that decrease as the number of nucleons increase. The radii of the largest size nuclei can be observed experimentally by electron microscopes as confirmation of the theoretical calculations.
Keywords: urban flora; urban ecosystem; species occurrence frequency; Shannon index; biodiversity complexity; biodiversity potential.; density; electron; Radius; Electron Neutrino; Proton; Neutron; Up Quark; Down Quark; Table of Nuclear radiuses and densities.